Acceptability of an argument in the mathematical classroom: the role of beliefs - Saccoletto, Marta (LUMAT-B: International Journal on Math, Science and Technology Education, 2024)
The study focuses on upper secondary students’ beliefs which emerge in students’ evaluating of solutions strategies and of the connected arguments proposed by their peers. In particular, an activity aimed to introduce the concept of classical probability and based on the Problem of Points is considered. The thematic analysis is conducted on students’ protocols and on transcriptions of whole class discussions. Five themes of beliefs are defined. The analysis shows a great variety of beliefs which are crucial to evaluate others’ solutions and arguments, but not sufficient to reject incorrect solutions. The themes of beliefs are confronted with Goldin’s categories to highlight their variety.